Executive remuneration under the EU law and the Turkish law - Özcanlı, Fatma Beril (Leiden University, European and International Business Law (Advanced LL.M.), 2018)
Commission’s proposal on the amendment of the Shareholders Rights Directive points that the regime under the current remuneration system based on the alignment of the shareholders’ interest with the company’s’ is not working out anymore. With regards to that fact the proposal suggested amendments to enhance shareholders oversight. These amendments can be identified as the promotion of the say on pay on the remuneration policy and remuneration report. And furthermore, the previous Recommendations have also set the criteria to determine the amount of remuneration. On the other hand the regime under the Turkish Law is quite different than the EU-system. Remuneration of the directors can be designed based on a general assembly meeting decision or on a provision in the articles of association of the company. Besides the corporate governance principles, there is no criteria set for the companies to determine the material amount of the remuneration.
Leiden University, European and International Business Law (Advanced LL.M.) Dissertation
Keywords: executive pay systems; remuneration; principal-agent conflict; EU Law; Shareholders Rights Directive; remuneration policy; remuneration report; TCC remuneration system; comparison